Population dynamics of Aceria litchii (Keifer) (Acari: Eriophyidae) reveals differential responses of lychee varieties - Amaral, I [UNESP]; Matta, L. G. [UNESP]; Andrade, D. J. [UNESP] (Systematic & Applied Acarology Soc London, Natural History Museum, 2020)
Lychee productivity (Litchi chinensis) has been decreasing since the appearance of the erinose mite Aceria litchii (Keifer) in the main producing regions. This mite causes erinose formation in leaflets, branches, and fruits, which affects fruit productivity and quality. This study referred to an assessment of the population dynamics of this mite associated with abiotic factors in different lychee varieties during 25 months. For the assessments, the germplasm bank of the Faculty of Agrarian and Veterinary Sciences, UNESP-Jaboticabal, state of Sao Paulo, with lychees in full production was used. The assessed varieties were Bengal, Americana, Brewster, Groff, and WB4. Aceria litchii occurred in lychee plants over the years, reaching the highest levels in October and November. These results are considered important for the establishment of a more adequate management program for A. litchii. In this study, we verified that the Bengal variety (widely commercialized) is one of the varieties more susceptible to the mite attack. The variety Americana showed resistance to the mite. Despite the occurrence records for the pest in this variety, the number of individuals and, consequently, the erinose was reduced. Information reported here on the relationships between lychee varieties and the main crop pest is essential to implement plant-breeding programs or even select resistant or tolerant varieties to the erinose mite.
Keywords: productivity; erinose; Bengal and Americana